Israel vs. the PLO [videorecording] the invasion of Lebanon - Jessup, Ted; Westin, AV (Great TV news stories, 1989)
The story of Israel's 1982 attempt to obliterate a formidable enemy; of the bloody attack on Beirut; of the innocent civilians caught tragically in the crossfire; and of the horrible price paid when Israel changed from David to Goliath.